An Analysis of Demonstrations on Rapeseed in District Ferozepur of Punjab (Indian Journal of Extension Education, 2024)
Punjab Agricultural University Farm Advisory Service Centre, Ferozepur conducteddemonstrations on rapeseed (gobhi sarson variety GSC 7) on farmer’s fields in districtFerozepur during rabi seasons (October to March) during the years 2019-20, 2020-21,2021-22 and 2022-23 in 20.71 ha area, respectively. Punjab Agricultural Universityrecommended variety GSC 7 of gobhi sarson with improved agricultural practices indemonstration plots produced significantly higher grain yields of 22.4, 22.2, 20.1, and 21.3q ha-1 as compared to 17.2, 14.8, 15.6, and 17.8 q ha-1 in check plots during rabi 2019-20,2020-21, 2021-22 and 2022-23, respectively. Demonstration plots recorded an averageincrease in yield of 24.5 per cent over check plots. The average extension gap, technologygap, and technology index were 5.2 q ha-1, 3.5 q ha-1, and 14.0 per cent, respectively. Ahigher average net return of Rs. 73511.3 ha-1 was obtained in demonstration plots, whichwas 30.9 per cent greater than check plots with a net return of Rs. 50768.8 ha-1.